SELF-CARE ACTIVITIES OF PATIENTS UNDERGOING MAINTENANCE HEMODIALYSIS IN ERBIL GOVERNORATE - Ali, Sideeq Sadir (Journal of Sulaimani Medical College, 2021)
Background Self-Care activities of hemodialysis patients are very important on a daily base, which improve their health and prevent them from complications and illness. This practice was the best practice that used since Orem’s nursing theory until now to improve all sides of patients. Objectives This study aims to assess the level of Self-Care activities and determines the association factors affecting their activity among hemodialysis patients. Materials and Methods This cross-sectional study involved 242 patients that maintain on the hemodialysis treatment in Erbil City from November 2019 to April 2020, by using interview questionnaires. Data were analyzed by SPSS Program version 23 involved descriptive statistics, including frequency, percentage, and chi-square tests. Results More than half of the participants (55.4%) were in the older adult age group, male (52.5%), illiterate (53.7%), and live in the urban area (54.5%). The majority of them were married (72.3%) and poor income (76%). Highly percentage were non- smokers (94.6%), 88.8% were with chronic diseases and hypertension (72.7%). 50.4% of them time duration of hemodialysis treatment was between 1 year to 4 years. Most of the participants (70.2%) sometimes they were done self-care activities. Dependency of self-care activities was significantly higher associated with all the variables of socioeconomic (P <0.001) except with sex, however, there was no significant association with all the variables of clinical data except with associated disease of Chronic Renal Failure, the existence of heart disease and with a duration of hemodialysis treatment. Conclusion In general, hemodialysis patients sometimes can perform self-care activities. Dependency of self-care activities was highly significantly associated with the majority of socioeconomic variables and with the few parts of the clinical variable. Hemodialysis patients need their self-care activities for improving their health and well-being continually.
Keywords: Self-care; Activities; Hemodialysis; Dependency; Patient